Umbilical cord milking-benefits and risks - Koo, Jenny; Kilicdag, Hasan; Katheria, Anup (Frontiers in Pediatrics, 2023)
The most common methods for providing additional placental blood to a newborn are delayed cord clamping (DCC) and umbilical cord milking (UCM). However, DCC carries the potential risk of hypothermia due to extended exposure to the cold environment in the operating room or delivery room, as well as a delay in performing resuscitation. As an alternative, umbilical cord milking (UCM) and delayed cord clamping with resuscitation (DCC-R) have been studied, as they allow for immediate resuscitation after birth. Given the relative ease of performing UCM compared to DCC-R, UCM is being strongly considered as a practical option in non-vigorous term and near-term neonates, as well as preterm neonates requiring immediate respiratory support. However, the safety profile of UCM, particularly in premature newborns, remains a concern. This review will highlight the currently known benefits and risks of umbilical cord milking and explore ongoing studies.